STUDI EMISI KARBON DIOKSIDA DARI TIGA JENIS LAHAN GAMBUT DI DESA TANJUNG LEBAN DAN SEPAHAT KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Edo Furnando; Tengku Ariful Amri; Sofia Anita (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The high  concentration of carbon  dioxide  in the atmosphere  is suspected  as the main cause  of global  warming,  therefore,  the carbon balance  is very  important  to  investigate. At this time, tropical peatlands are used as agricultural cultivation and plantation, one of them is in  Bengkalis,  Riau Province.  This study aimed  to measure  the concentration of CO2 based on  the relationship  of physical and  chemical  properties of  peat.  Measurements  were performed on  peatlands  which have  different  vegetation cover,  i.e. bush  land, oil palm  plantation,  and  secondary  forest.  The used method in this study  are Infrared  Gas  Analyzer  and  Gas Chromatography.  The average of obtained emissions based on  the effect  of  water table,  peat  temperature,  and  pH  (H2O)  of  bush  land, oil palm  plantation, and secondary forest  are  497,4  ppm,  523,2  ppm, and  457,2  ppm, respectively.